In Situ Nanoscale Imaging of Struvite Formation during the Dissolution of Natural Brucite: Implications for Phosphorus Recovery from Wastewaters - Hoevelmann, J.; Putnis, Christine (American Chemical Society, 2016)
As phosphorus (P) resources are diminishing, the recovery of this essential nutrient from wastewaters becomes an increasingly interesting option. P-recovery through the controlled crystallization of struvite (MgNH4PO4·6H2O), a potential slow-release fertilizer, is highly attractive, but costly if large amounts of Mg have to be added. In this context, natural Mg-minerals like brucite (Mg(OH)2) could provide more cost-effective Mg-sources compared to high-grade Mg-compounds such as MgCl2. Here we used in situ atomic force microscopy (AFM) to study the interactions of ammonium phosphate solutions with brucite (001) cleavage surfaces. Brucite dissolution was strongly enhanced in the presence of H2PO4(-) ions, most likely due to the formation of negatively charged surface complexes. Simultaneously with brucite dissolution, we directly observed the formation of a new phase that was identified as struvite by Raman spectroscopy. Our results suggest that brucite dissolution and struvite precipitation were coupled at the mineral-fluid interface within a thin fluid boundary layer. An interpretation is proposed where the heterogeneous nucleation and growth of struvite occurs via a particle-mediated process involving the formation of primary nanoparticles, followed by their continuous aggregation, fusion and possible transformation to crystalline struvite. These observations have implications for the feasibility of using brucite in phosphorus recovery processes.